Determination of the Rayleigh damping coefficients of steel bristles and clusters of bristles of gutter brushes (2015)
Street sweeping is an important service that is usually performed by lorry-type vehicles that have a gutter brush, which is comprised of clusters of steel bristles that sweep the debris found in the road gutter. Effective operation of this brush is important, as most of the debris on roads is located in the gutter. In order to model a gutter brush by means of finite element dynamic analyses, it is necessary to determine appropriate values of the Rayleigh damping coefficients of both individual bristles and clusters of bristles. This paper presents the methodology and results of experimental tests that have been conducted to determine these coefficients. The results obtained are useful when studying the performance of conventional and oscillatory street sweeper gutter brushes by means of dynamic finite element modeling.